1993
DOI: 10.1002/etc.5620120816
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two freshwater turtle species as monitors of radionuclide and chemical contamination: DNA Damage and residue analysis

Abstract: Two species of turtles that occupy different ecological niches were compared for their usefulness as monitors of freshwater ecosystems where both low-level radioactive and nonradioactive contaminants are present. The pond slider (Truchemys scri tu) and common snapping turtle (Chelydra serpentinu) were analyzed for the presence of 90Sr, ' 7Cs, 60Co, and Hg, radionuclides and chemicals known to be present at the contaminated site, and single-strand breaks in liver DNA. The integrity of the DNA was examined by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Radiation and other carcinogens are known to cause genetic damage [5][6][7][8][9][10][11][12][13]. However, few studies have investigated DNA damage in relation to radionuclides in natural settings [14][15][16][17][18]. However, studies that examine genetic damage in natural populations provide useful information about the potential biological hazards associated with such toxic agents and the amelioration or exacerbation of effects via ecological pathways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiation and other carcinogens are known to cause genetic damage [5][6][7][8][9][10][11][12][13]. However, few studies have investigated DNA damage in relation to radionuclides in natural settings [14][15][16][17][18]. However, studies that examine genetic damage in natural populations provide useful information about the potential biological hazards associated with such toxic agents and the amelioration or exacerbation of effects via ecological pathways.…”
Section: Introductionmentioning
confidence: 99%
“…The alkaline unwinding technique is a rapid method of assessing strand breaks. Recent studies have shown that the number of breaks, as determined from this method, can be associated with various toxic agents [11][12][13][14][15]26].…”
Section: Introductionmentioning
confidence: 99%
“…These assays are being developed and used in fish [16][17][18], but few assays have been adapted for alternate aquatic species. Most of these assays use either alkaline elution techniques [19] or alkaline unwinding followed by fluorometric detection [20]. These techniques have the advantage of being rapid, relatively inexpensive, and requiring little specialized instrumentation other than a spectrofluorometer.…”
Section: Introductionmentioning
confidence: 99%
“…Neither of these assays, however, directly quantifies DNA strand lengths, in particular the strand lengths of double-stranded DNA. Data from alkaline elution and/or unwinding techniques are expressed as an F-value, which represents either the fraction of double-stranded DNA present following alkaline unwinding [16,20] or a strand-scission factor calculated from alkaline elution kinetics [19].…”
Section: Introductionmentioning
confidence: 99%
“…Among the many assays that have been developed for the assessment of DNA damage, alkaline unwinding and agarose gel electrophoresis are reported to be efficient and rapid methods for evaluating various toxic agents [5,16]. Researchers have demonstrated the association between various toxic agents, including heavy metals and radionuclides, and DNA in natural populations using alkaline unwinding techniques [5,17]. This procedure has proven to be useful for assessing the number of DNA strand breaks.…”
Section: Resultsmentioning
confidence: 99%